2023
DOI: 10.1037/edu0000792
|View full text |Cite
|
Sign up to set email alerts
|

Preservice teachers’ epistemic and achievement emotions when confronted with common misconceptions about education.

Abstract: Learning processes that involve cognitive incongruity are closely tied to emotional experiences such as curiosity or confusion. The present study examined how discovering that a confidently held misconception is incorrect influences emotions and in turn the motivation to seek additional information. We asked 275 preservice teachers to judge if common statements about education were true or false and provided feedback about whether these statements were supported by scientific evidence. Following feedback, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…2). Berweger et al (2023), found that emotions, such as surprise, confusion, and anger, play a role in information-seeking when pre-service teachers had to face-up to misconceptions about education. They conclude that their study:…”
Section: Psychology Of Emotionsmentioning
confidence: 99%
“…2). Berweger et al (2023), found that emotions, such as surprise, confusion, and anger, play a role in information-seeking when pre-service teachers had to face-up to misconceptions about education. They conclude that their study:…”
Section: Psychology Of Emotionsmentioning
confidence: 99%